Kajian Daya Tampung dan Mutu Kelas Air Daerah Aliran Sungai Banjir Kanal Timur, Kota Semarang - Thomas Triadi Putranto; Novie Susanto (Department of Urban and Regional Planning, Diponegoro University, 2019)
The increasing population every year and the rapid economic development in Semarang City caused environmental problems related to the water resources used. One of the impacts of environmental problems is the lowering water quality of the Banjir Kanal Timur (BKT) Watershed. The study aims to identify the potential and conditions of the BKT watershed, and river segmentation as a basis for determining representative monitoring points that are used to determine the capacity that is adjusted to the description of river water segmentation class. The methods were descriptive and quantitative analysis approach based on the observation and measurement in the field campaign as well as the laboratory analysis. In addition, this research was also compiling the QUAL2E modeling to determine estimation of contamination load and capacity of contamination of Banjir Kanal Timur. The results conducted that the BKT has poor water quality based on the parameters of DO, BOD, and fecal coliform, while for the NO3 and NO2 parameters indicate good water quality. Segment that has load capacity of BOD contamination is segment 1. Segments that have load capacity of Nitrite (NO2) and Nitrate (NO3) contents are segment 1 to segment 4. The segment which has load capacity of contamination of fecal coliform is segment 2. Thus, Segment 1 can be classified into second class while segment 2 goes into third class. Furthermore, segment 3 and 4 are into fourth class respectively.